Independent or simultaneous lowering of core and skin temperature has no impact on self-paced intermittent running performance in hot conditions - Thomas, G.; Cullen, T.; Davies, M.; Hetherton, C.; Duncan, B.; Gerrett, N. (European Journal of Applied Physiology, 2019)
Purpose: To investigate the effects of lowering core (Tgi) and mean skin temperature (Tsk) concomitantly and independently on self-paced intermittent running in the heat. Methods: 10 males (30.5 ± 5.8 years, 73.2 ± 14.5 kg, 176.9 ± 8.0 cm, 56.2 ± 6.6 ml/kg/min) completed four randomised 46-min self-paced intermittent protocols on a non-motorised treadmill in 34.4 ± 1.4 °C, 36.3 ± 4.6% relative humidity. 30-min prior to exercise, participants were cooled via either ice slurry ingestion (INT); a cooling garment (EXT); mixed-cooling (ice slurry and cooling garment concurrently) (MIX); or no-cooling (CON). Results: At the end of pre-cooling and the start of exercise Tgi were lower during MIX (36.11 ± 1.3 °C) compared to CON (37.6 ± 0.5 °C) and EXT (36.9 ± 0.5 °C, p < 0.05). Throughout pre-cooling Tsk and thermal sensation were lower in MIX compared to CON and INT, but not EXT (p < 0.05). The reductions in thermophysiological responses diminished within 10-20 min of exercise. Despite lowering Tgi, Tsk, body temperature (Tb), and thermal sensation prior to exercise, the distances covered were similar (CON: 6.69 ± 1.08 km, INT: 6.96 ± 0.81 km, EXT: 6.76 ± 0.65 km, MIX 6.87 ± 0.70 km) (p > 0.05). Peak sprint speeds were also similar between conditions (CON: 25.6 ± 4.48 km/h, INT: 25.4 ± 3.6 km/h, EXT: 26.0 ± 4.94 km/h, MIX: 25.6 ± 3.58 km/h) (p > 0.05). Blood lactate, heart rate and RPE were similar between conditions (p > 0.05). Conclusion: Lowering Tgi and Tsk prior to self-paced intermittent exercise did not improve sprint, or submaximal running performance.